Leveraging Energy Efficiency of Smart Room using Blink System - Putra, I Gusti Ngurah Agung Wira Sattvika; Putra, I Gede Juliana Eka; Purnama, I Nyoman (International Journal of Informatics and Computation, 2025)
This research presents the prototype of an IoT-based automatic room temperature control system to improve energy efficiency within an office. The designed smart room system uses a NodeMCU ESP8266 microcontroller, a DHT22 sensor for monitoring temperature and humidity, a proximity sensor to detect occupancy, and an infrared blaster to control the AC. An LCD displays real-time data, and integration with the Blynk app allows remote monitoring. The system automatically adjusts the AC temperature based on room occupancy and turns off the AC after 45 minutes of inactivity. According to the experimental results, energy consumption before implementation was 88.1 kWh per week, dropping to 38.5 kWh after, achieving a 56.3% energy saving without reducing user comfort. These results show that the system is effective and cost-efficient for smart building applications.